SOSIALISASI PENGENALAN KONSEP DIRI SISWA PADA MASA PRA PUBERTAS - Dzaid, Ahmad; Nurhidayah, Siti (An-Nizam, 2024)
Children's self-concept is related to their ability to adapt and be accepted by their environment. Children who have positive self-confidence will have clear goals and aspirations for the future and have a strong fighting spirit and zest for life. Self-concept is an evaluation of certain aspects of oneself. Children can self-evaluate several aspects of their academic life. A person's perception of how others see them builds their self-concept. Lack of understanding of students' self-concept often hinders learning activities and processes. It is undeniable that students of SDN 01 Karang Indah, Bojongmangu Sub-district, can also experience self-concept problems caused by a lack of understanding about themselves. In connection with this, through community service activities, we seek psychoeducation on self-concept using the socialisation method by conducting this psychoeducation at SDN 01 Karang Indah, Karang Indah Village, Bojong Mangu District, Bekasi Regency. The results of community service show that the psychoeducation programme on knowing oneself towards self-development has the potential to provide understanding and increase knowledge to students of SD Negeri Karang Indah 01 in Karang Indah Village. This is evident from the pre-test and post-test results showing significant improvements in students' understanding of the material presented.